Red leaves - Simons, Paullina (Ney York, U.S.A. : St. Martin´s Paperbacks, 1997)
Everyone at Dartmouth College knowa Kristina Kim, Conni, Tobias, Albert Maplethorpe, and Jim Shaw. Attractive, intelligent, and poised for brillant futures, they are campus elite, and ever since freshman year, they've been inseparable -almost like family. Led by the beautiful, spirited and enigmatic Kristina, they share an intimacy others envy.
CONTENTS Prologue I PART I THE GIRL IN THE BLACK BOOTS 1. Sunday 7 2. Monday 64 3. Tuesday 105 PART II SPENCER PATRICK O'MALLEY 4. In the Woods and on the Wall 143 5. Close friends 186 6. Disposition of the Estate 245 7. Constance Tobias 298 8. Once upon a time in Greenwich, Connecticut 339 9. Red leaves 357 EPILOGUE 401
Incluye Contents
Incluye Prologue
Incluye Epilogue
International Bestselling Author of Tully
Keywords: ENGLISH LITERATURE; STORY; SUSPENSE STORY; AMERICAN LITERATURE